Analysis of the Movements in Sigeh Penguten Dance Using Labanotation: Benefits and Challenges in Documenting Traditional Dance - Habsary, Dwiyana; Nabila Kurnia; Indra Bulan (ICSIGER- International Conference on Science and Emerging Technology, 2025)
This study aims to analyze the movements of the Sigeh Penguten Dance using Labanotation as an effort to document and preserve the traditional dance of Lampung. Labanotation, as a universal movement notation system, provides a structural approach to understanding the dynamics, directions, and qualities of movement in a dance. Through a qualitative descriptive method, this research observes the main movement patterns of the Sigeh Penguten Dance and translates them into Labanotation symbols. The results show that the use of Labanotation can provide a more systematic representation of the movement structure, floor patterns, and classification of dancers’ body movements. The main benefits of applying this notation include ease of documentation, learning, and intergenerational knowledge transfer. However, the study also identifies several challenges, including the complexity of interpreting traditional movements rich in symbolic meaning into a Western notation system, limited understanding of notation symbols among dance practitioners, and the need for specialized training for researchers and dancers. Therefore, integrating Labanotation with contextual cultural understanding is essential to maintain the authenticity and meaning of dance movements. This research is expected to contribute to the development of more scientific and sustainable methods for analyzing and documenting Indonesian traditional dances. Keywords: Sigeh Penguten Dance, Labanotation, Movement Analysis, Dance Documentation, Cultural Preservation.